COMPARATIVE ANALYSIS OF AUTOMATIC LAYER-BY-LAYER SEGMENTATION USING OPTICAL COHERENT TOMOGRAPHS DRI OCT AND RETINASCAN-3000 IN HEALTHY PATIENTS - M. M. Bikbov; R. R. Fayzrakhmanov; T. R. Gil’manshin; R. M. Zainullin; R. I. Hikmatullin; M. R. Kalanov (Oftalʹmologiâ, 2017)
The aim was to determine different possibilities and the operating principle of modern optical coherent tomographs OCT RETINASCAN-3000 and  DRI OCT TRITON in automatic layer-by-layer segmentation of the  retina  and  perioretinal  structures. Methods. The study involved 31 patients (31  eyes) with no retinal pathology in the  macular area. Of these, there were  13 men,  18 women.  The average age  of the  patients was  55.8±3.65  years. Each patient  was  followed by a layered  automatic structuring of the  central  retina  with the help of RetinaScan-3000 (Nidek Technologies)  (1st  group,  n = 31)  and DRI OCT Triton (Topcon Japan) (2nd group,  n = 31)  of the right eye only. The OST device RetinaScan-3000 used  the  mode  macula  multi cross 6 mm,  the  DRI OCT Triton used  the  5 line cross 6 mm mode.Results: The difference in the automatic layer-by-layer segmentation between the optical coherent tomographs DRI OCT TRITON and OCT RETINASCAN-3000 is, first of all, in the unequal coverage of the retina  layers and the preand subretinal space and the number of automatically layered zones.  For example,  OCT RETINASCAN-3000 (SD-OCT) suggests the separation of the transverse optical  section  of the  structures of the  posterior segment of the  eyeball into 5 structural zones  when,  as  DRI OCT TRITON in (SSOCT), further  clearly  isolates  the  preretinal structures  and  the  choroid,  delineating  the  border of the  sclero-choroidal Articulation. The DRI OCT Triton device in the  SS-OCT system allowed for a more  complete differentiation from the  position of layered  delimitation of the  retina  covering  6 retinal  zones  to obtain  digital values  for  coverage of 5 layers  on RetinaScan-3000 (SD OCT).Conclutions: The DRI OCT Triton device with SS-OCT technology has  more  possibilities for topical diagnostics of the  posterior eyeball structures in the autonomous mode  relative to the Retinascan-3000 with SD-OCT technology.